Horizontal convergence as a factor for forecasting fog or stratus (MAUSAM, 1962)
Influence of horizontal eenvernce in the surface layers bounded by thermal inversion on formation of  radiation fog at Palam, Santacruz and Begumpet during the winter 1960-61 is studied in this note.